Pedagogical Commitment of Teachers and Cognitive Mastery of Students in Public Elementary Schools - , Daneth M. Alvar; , Josephine B. Baguio (Archives of Current Research International, 2025)
This study aimed to determine the significant relationship between the pedagogical commitment of teachers and the cognitive mastery of students in public elementary schools in Baganga District, Division of Davao Oriental. Specifically, it sought to assess how various dimensions of pedagogical commitment, namely instructional effectiveness, student-centered approach, continuous professional development, and professional dedication—predict student cognitive mastery. A descriptive-correlational research design was employed, involving 138 public elementary school teachers selected through stratified random sampling. Data were collected using standardized questionnaires administered via face-to-face surveys. The analysis utilized mean, standard deviation (SD), Pearson product-moment correlation, and multiple linear regression techniques to determine the relationship and predictive value of the variables. The findings revealed that both the pedagogical commitment of teachers and the cognitive mastery of students were rated as very high. A significant positive relationship was established between the two constructs. Among the dimensions of pedagogical commitment, instructional effectiveness, student-centered approach, and continuous professional development significantly influenced students’ cognitive mastery, while professional dedication showed no significant impact. These results suggest the need for school administrators to prioritize instructional practices and professional growth opportunities that directly enhance students’ learning outcomes. The study underscores the importance of fostering teacher development initiatives aligned with student learning goals, thus contributing to evidence-based educational planning and professional development in public elementary schools.